Malay abstractions of ecological patterns into geometricised expressions in palatial architecture and the applied arts / Nurhaya Baniyamin...[et al.] - Baniyamin, Nurhaya; Jasmani, Ismail; Jahn Kassim, Puteri Shireen (Universiti Teknologi MARA, Kedah, 2020)
Malay ornamental traditions are more generally known for their curved, expressive and convoluted patterns, emerging from the traditions of woodcarvers and artisans in observing ecological forms, rather than geometric or gridded patterns. Typically, observed flora and fauna are developed into curvatures and ornate forms and translated into panels and ‘papan larik’ in vernacular, including palatial, architecture. This paper highlights a lesser known tradition in Malay architectural decorative traditions in which such ecological forms are abstracted into more geometrized elements, either due to the modularity needed for insertion as architectural elements, using techniques such as weaving, or modern techniques encountered bye craftsmen and builders; such as metallurgy. The paper highlights five examples in the palaces of Kedah, Perak, Kelantan, Terengganu and Selangor, and examples of geometricized elements are also observed in applied arts. These highlights the essence of the Malay culture and civilization have a resource in both organic and geometric patterns evolvement which reflect a form of rationality and simplified geometric form, which had arisen from more traditional patterns such as weaving and paneling. The findings of the paper contribute to the availability of the range of expressions in Malay traditions in more modular design and format available for regional and localized identity in present modern buildings and developments.